ANALYSIS OF THE FACTORS INFLUENCING BUYING DECISION OF CELL PHONE ACCESSORIES AT BINTANG STORE IN MANADO - Brandon Zainal; Willem J. F. A. Tumbuan; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The study aims to analyze the various factors that influence consumers' decision-making process when purchasing cellphone accessories at Bintang Store, understanding the determinants that shape consumers' choices is crucial for retailers seeking to optimize their marketing strategies. By identifying and examining these factors (are Price, Product Completeness, and Location), store can tailor their offerings efforts to meet consumer preferences effectively. This research utilizes quantitative techniques. The collected data is then analyzed using IBM SPSS 22 Program, including multiple regression analysis. The findings shed light on the relative importance of different factors in influencing consumers' decision-making processes when purchasing cellphone accessories. Furthermore, they provide valuable insights into the specific attributes and characteristics that drive consumer behavior in this context. Overall, this research contributes to the existing literature on consumer behavior and decision-making processes in the context of cellphone accessories. By analyzing the factors that influence consumers' choices at Bintang Store, this study provides practical recommendations for the store looking to enhance their understanding of consumer preferences and optimize efforts.   Keywords: price, product completeness, location, buying decision